Association of biliary microflora dysbiosis with cholangiocarcinoma: a single-center study - Wang, Xiangyu; Liu, Xue; Niu, Wang; Guan, Chenyue; Liu, Chunlong; Yu, Jiangtao; Song, Kun (Frontiers in Microbiology, 2025)
BackgroundCholangiocarcinoma (CCA) is an aggressive malignancy that poses a serious threat to long-term survival. In this study, we compared the biliary microbiota and metabolomic profiles of patients with CCA and those with choledocholithiasis to identify characteristic microbial species and metabolites associated with CCA and to explore the mechanisms linking microbial dysbiosis to CCA development.MethodsA total of 25 CCA patients and 25 choledocholithiasis patients were included in the study. Bile was collected intraoperatively and analyzed using 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC–MS) to investigate the correlation between specific microorganisms and metabolites by integrating microbiomics and metabolomics.ResultsThe abundance and diversity of microorganisms were similar between the two groups; however, their microbial compositions were significantly different. Microbial–metabolite interactions may contribute to CCA development through pathways such as inflammation, oxidative stress, and energy metabolism.ConclusionThese findings reveal a unique microbial community structure and metabolic profiles in CCA patients, providing potential microbial and metabolic markers for early CCA diagnosis. They also lay a theoretical foundation for the development of novel therapeutic strategies.